A comparative study of geometry-based methods and intra-arterial pressure measurements to assess the hemodynamic significance of equivocal iliac artery stenoses. (April 2019) - Heinen, Stefan GH; Huberts, Wouter; van den Heuvel, Daniel AF; van de Vosse, Frans N; de Vries, Jean-Paul PM; Delhaas, Tammo
Objectives: To date, the ultimate decision to treat iliac artery stenoses in patients suffering from symptomatic peripheral arterial disease is based on the patient's symptoms and on visual inspection of angiographical images. The primary aim of this study was to investigate the accuracy of geometry-based methods (i.e. visual inspection and quantitative vascular analysis (Viewforum version R7.2v1 Advanced vessel analysis, Philips Healthcare, Best, The Netherlands) of 3D rotational angiography) to identify the severity of equivocal iliac artery stenosis in peripheral arterial disease patients with intra-arterial hyperemic pressure measurements (gold standard) as a reference. Methods: Twenty patients with symptomatic iliac artery stenoses were subjected to 3D rotational angiography. Intra-arterial pressure measurements under hyperemic conditions were performed across 24 visually identified iliac artery stenoses. Three experienced interventional-radiologists retrospectively estimated the lumen diameter reduction by visual inspection. Furthermore, quantitative vascular analysis was performed on the 3D rotational angiography data. Geometry-based estimates were classified into two groups: lumen diameter reduction of <50% (non-significant) and diameter reduction≥ 50% (significant), and compared to the intra-arterial hyperemic pressure gradients. A stenosis causing a pressure gradient (Δp) ≥10 mmHg was considered hemodynamically significant. Results: Visual inspection and quantitative vascular analysis correctly identified hemodynamically significant stenoses in, respectively, 83% and 67% of the 24 iliac artery stenoses. Quantitative vascular analysis-based identification of hemodynamic significant stenoses (Δp ≥ 10 mmHg) could be optimized by lowering the threshold to a 42% lumen diameter reduction which improved the accuracy from 67% to 83%. Conclusions: Visual inspection of 3D rotational angiography by experienced interventional-radiologists has an 83% accuracy to identify hemodynamic significant iliac artery stenoses (Δ p ≥10 mmHg). The use of quantitative vascular analysis software did not improve accuracy.